Impacto en la población adulta mayor de la política pública del distrito metropolitano de Quito implementada por el centro de la experiencia del adulto mayor CEAM centro, historia de vida de dos usuarias, periodo 2010-2013 - Estrella Landázuri, Amparito del Pilar (2015)
The Thesis starts with the analysis of the life cycle of human beings process, with an emphasis on maturity age stage, bio psychosocial changes they faced with, characteristics, appropriate conditions of this phase and the challenge of accepting and integrate it as our own. It explores the theoretical elements, terms and social concepts about older age adults or seniors, bearing in mind the concept on themselves and what it means to age in a healthy way, also the different development theories for this population group in the areas: biological, psychological and social. This allowed us to sensitize the real attitude that we must show to these people, knowing that everyone, without exception, will go through this vital process. According with the public policy there some aspects that help us to integrate and structure it, in the same way it will responds to the political regime and Government project, in this case to the paradigm of the Proper Living Way. Besides we analyze both subjects the level of citizen participation and the seniors as active subject of their rights. Another aspect to consider is the demographic, this aspect is in direct impact in the Senior Population, two situations has influence in this aspect: the extension of life expectancy and the strong increase of number in this population group. In addition, we conducted a review of the national legal framework and international agreements that are responsible for the proper attention to be given to this group that need a priority attention. Finally, with the support of the Public Policy applied in our country for Seniors, in both fields national and local, and we are making special emphasize in The Senior Experience Center (CEAM-Center), we complete our investigation of the topic using two true life stories from Seniors that are part of the daily services in this Center